PERANCANGAN SISTEM INFORMASI TEMPAT WISATA SEBAGAI MEDIA PROMOSI DI KABUPATEN BIMA - tyas tyas; Tyas mayang sari; Syarifuddin; Hilyatul Mustafida (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Bima Regency has substantial natural, cultural, and culinary tourism potential, but the dissemination of tourism information remains limited because promotion by the Bima Regency Tourism Office still relies on social media and printed brochures with limited reach and infrequent updates. This study aimed to design and implement a website-based tourism information system as a digital promotion medium for Bima Regency and to measure its user experience using the System Usability Scale (SUS) method. The system was developed using the prototyping method, comprising the communication, quick plan, modeling quick design, and construction of prototyping stages, and was built with the Laravel framework and a MySQL database. It provides two access levels: an administrator who manages destination data, categories, and photo galleries, and visitors who can browse destination information through public pages. Black Box Testing on fourteen main function scenarios showed that all functions performed as expected. SUS testing yielded an average score of 92.5 (Grade A, Excellent) for administrators and 62.27 (Grade D, OK/Fair) for visitors. These results indicate that the system is acceptable and operates well, although the visitor-side user experience still needs improvement through better display consistency and clearer navigation.